2007
DOI: 10.1007/s11837-007-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of bulk ultrafine-grained zirconium by accumulative roll bonding

Abstract: Research Summary Current Refractory Metals ResearchThis work demonstrates that bulk ultrafi ne-grained zirconium can be fabricated by accumulative roll bonding. Grain refi nement takes place by geometrical thinning and grain subdivision through the formation of geometrically necessary boundaries. This is consistent with the stabilization of a typical rolling texture during processing and with the absence of any recrystallization texture components. The ultrafi ne-grained zirconium possesses high ultimate tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…[62,63] Monolithically rolled Zr develops texture with strong intensities associated with {0001} that are tilted • away from the normal direction (ND) about the rolling direction (RD). [40,64,65] The textures of our Zr-Nb nanolayered composites (Figure 2) clearly exhibit the same predominant features of monolithic rolling textures within normal variation. Moreover, prior modeling studies that calculated the relative contributions of the different deformation modes clearly showed that these Zr and Nb rolling textures are a consequence of dislocation slip.…”
mentioning
confidence: 58%
“…[62,63] Monolithically rolled Zr develops texture with strong intensities associated with {0001} that are tilted • away from the normal direction (ND) about the rolling direction (RD). [40,64,65] The textures of our Zr-Nb nanolayered composites (Figure 2) clearly exhibit the same predominant features of monolithic rolling textures within normal variation. Moreover, prior modeling studies that calculated the relative contributions of the different deformation modes clearly showed that these Zr and Nb rolling textures are a consequence of dislocation slip.…”
mentioning
confidence: 58%
“…Chemical sharpness of the interfaces at this length scale was explored in a previous publication [43] and indicated that the interfaces were chemically sharp, despite the mechanical straining and intermediate annealing treatments. Bright Field TEM was performed using a Tecnai F30 (FEI, Hillsboro, OR, USA) electron microscope operating at 300 kV on cross-sectional samples viewed along the transverse direction (TD).…”
Section: Experimental Methodsmentioning
confidence: 91%
“…For instance, their rolling textures after straining with or without subsequent annealing have been reported [43][44][45] and will be discussed in the results section of this paper. When combined with polycrystalline modeling for texture and stress-strain behavior, the plastic deformation mechanisms activated in rolling and other modes of deformation have been deduced.…”
Section: Introductionmentioning
confidence: 97%
“…The volume is compressed in the normal direction (ND), extended in the rolling direction (RD) and constrained from deforming in the transverse direction (TD). The velocity gradient tensor associated with PSC is: (Jiang et al, 2008;Jiang et al, 2007;Linga Murty and Charit, 2006;Philippe, 1994;Philippe et al, 1995;Zhu et al, 2005). Using the initial texture as input, these deformation textures have been successfully predicted using both mean-field polycrystal plasticity models (Knezevic et al, 2014e) as well as the crystal plasticity finite element model used here (Ardeljan et al, 2014a).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%